2020
DOI: 10.7554/elife.52677
|View full text |Cite
|
Sign up to set email alerts
|

Brain aging comprises many modes of structural and functional change with distinct genetic and biophysical associations

Abstract: Brain imaging can be used to study how individuals’ brains are aging, compared against population norms. This can inform on aspects of brain health; for example, smoking and blood pressure can be seen to accelerate brain aging. Typically, a single ‘brain age’ is estimated per subject, whereas here we identified 62 modes of subject variability, from 21,407 subjects’ multimodal brain imaging data in UK Biobank. The modes represent different aspects of brain aging, showing distinct patterns of functional and stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(106 citation statements)
references
References 57 publications
5
101
0
Order By: Relevance
“…1. In line with existing findings about sex differences such as post-menopausal accelerated brain ageing [40], stratification by sex was also conducted in this study. The images were acquired at 1mm isotropic resolution using a 3D MPRAGE Sequence [18] and processed using the UK Biobank pipeline [41].…”
Section: Data and Preprocessingmentioning
confidence: 75%
See 1 more Smart Citation
“…1. In line with existing findings about sex differences such as post-menopausal accelerated brain ageing [40], stratification by sex was also conducted in this study. The images were acquired at 1mm isotropic resolution using a 3D MPRAGE Sequence [18] and processed using the UK Biobank pipeline [41].…”
Section: Data and Preprocessingmentioning
confidence: 75%
“…Through utilising a CNN we are able to create a model that has freedom to investigate spatial signatures, rather than relying on spatial priors or target structures, in contrast to other methods proposed to explore brain age in the UK Biobank. In both [39] and [40] image-derived phenotypes are used to train a linear model to predict brain age, with the former using the IDPs to create a single estimate of brain age and in the latter they explore whether multiple modalities can produce distinct modes that relate to different processes involved in ageing and disease. These methods allow us to explore different aspects of ageing using multimodal data but they require prior choice of the IDPs whereas our method is able to consider the whole of the input image and therefore there is potential for our method to pick up on different types of changes compared to the IDP-based models, especially those with subtle changes.…”
Section: Introductionmentioning
confidence: 99%
“…With about 5000 training subjects, SFCN achieves 2.28 years MAE while 3D-ResNet with tensor regression achieves 2.58 years (Kolbeinsson et al, 2019). For the larger training set with more than 10,000 subjects, linear regression with multimodality IDPs (including fMRI and DTI features) achieves an MAE of 2.9 years (Smith et al, 2020(Smith et al, , 2019, whereas SFCN obtains the best MAE in UK Biobank with an MAE of 2.14 years.…”
Section: The Performance Of Sfcn In Uk Biobank Datamentioning
confidence: 99%
“…Our presented strategy achieves state-of-the-art results in brain age prediction. Table 3 shows a summary of previously reported brain age prediction MAE results (Kolbeinsson et al, 2019;Ning et al, 2018;Smith et al, 2020). To eliminate the effect of sample size differences (i.e., to make these comparisons as meaningful as possible), we trained SFCN with comparable training set sizes as the previous studies, and compared performance with those.…”
Section: The Performance Of Sfcn In Uk Biobank Datamentioning
confidence: 99%
“…Studies showed that individuals' chronological age can be predicted accurately from brain MRI scans . Brain age delta, the difference of a subject's predicted (brain) age and chronological age, is linked with a variety of biological factors within the healthy population (Smith et al, 2020b), and group differences can be found in disease populations (Cole et al, 2019;Kaufmann et al, 2019). Yet, accurate prediction of a subject's age in healthy population is still a challenging task.…”
Section: Introductionmentioning
confidence: 99%